John Colet on the Ecclesiastical hierarchy of Dionysius : a new edition and translation with introduction and notes - Colet, John, 1467?-1519 (Studies in medieval and Reformation traditions ;, 2013)
This first new edition in almost 150 years and first edition of the complete manuscript is edited critically, translated expertly, and provided with an apparatus that identifies a coherent center for Colet's theology and agenda for reform in Tudor England.